Time-resolved optically stimulated luminescence of Al 2 O 3: C for ion beam therapy dosimetry - Yukihara, Eduardo G.; Brons, Stephan; Tessonnier, Thomas; Jäkel, Oliver; Greilich, Steffen (Physics in medicine and biology, 2015)
The objective of this study was to characterize the time-resolved (TR) optically stimulated luminescence (OSL) from Al 2 O 3 :C detectors and investigate methodologies to improve the accuracy of these detectors in ion beam therapy dosimetry, addressing the reduction in relative response to high linear energy transfer (LET) particles common to solid-state detectors. Al 2 O 3 :C OSL detectors (OSLDs) were exposed to proton, 4 He, 12 C and 16 O beams in 22 particle/energy combinations and read using a custom-built TR-OSL reader. The OSL response ##IMG## [http://ej.iop.org/images/0031-9155/60/17/6613/pmb518111ieqn001.gif] $r_\textOSL$ , relative to 60 Co gamma dose to water, and the ratio between the UV and blue OSL emission bands of Al 2 O 3 :C (UV/blue ratio) were determined as a function of the LET. Monte-Carlo simulations with the multi-purpose interaction and transport code FLUKA were used to estimate the absorbed doses and particle energy spectra in the different irradiation conditions. The OSL responses ##IMG## [http://ej.iop.org/images/0031-9155/60/17/6613/pmb518111ieqn002.gif] $r_\textOSL$ varied from 0.980 (0.73 keV μ m −1 ) to 0.288 (120.8 keV μ m −1 ). The OSL UV/blue ratio varied by a factor of two in the investigated LET range, but the variation for 12 C beams was only 11%. OSLDs were also irradiated at different depths of carbon ion spread-out Bragg peaks (SOBPs), where it was shown that doses could be obtained with an accuracy of ±2.0% at the entrance channel and within the SOBP using correction factors calculated based on the OSL responses obtained in this study. The UV/blue ratio did not allow accurate estimation of the dose-averaged LET for 12 C SOBPs, although the values obtained can be explained with the data obtained in this study and the additional information provided by the Monte-Carlo simulations. The results demonstrate that accurate OSLD dosimetry can be performed in ion beam therapy using appropriate corrections for the OSL response.